Office Hours” versus “After Office Hours” presentation in ST-segment elevation myocardial infarction and its impact on door-to-balloon time and clinical outcome : findings from a single center registry - Ang, Wee Kiat (2017)
Aim: We evaluated the clinical characteristics, door-to-balloon (D2B) time and clinical outcomes of STEMI patients who presented during “office hours” and “after office hours in our single center registry.